Penerjemahan Novel Anak dari Bahasa Inggris ke Bahasa Indonesia - Dewi Susanti Siahaan (Program Studi Magister Linguistik Terapan UNJ, 2016)
This study aimed to analyze the forms of unequivalence, translation procedures andtypes of translation error in Diary of a Wimpy Kid Noveltranslated from English to Bahasa Indonesia. It was a qualitative research with content analysis method conducted in 2015. The data were collected through a thorough reading and analyzing as well both source text and target text that the sentences that has error(s) in it. The data analysis and interpretation indicates that the deviation found to be the most (64,3%), followed by modification (12,8%), omission (12,8%),addition (5,72%), inversion (4,3%) and The findings lead to the recommendation to understand things beyond the text, practice continuous critic analysis learning method with various texts in the class in order to sharpen the ability to translate. Keywords: Errors In Translation, Translation Procedures, Forms Of Equivalence And Content Analysis. Abstrak. Penelitian ini bertujuan untuk menganalisis bentuk ketidaksepadanan yang terjadi,prosedur penerjemahan danjenis kesalahan penerjemahan yang terdapat dalam novel Diary si Bocah Tengil. Penelitian ini menggunakan pendekatan kualitatif dengan metode anaisis isi yang dilaksanakan pada tahun 2015.Data dikumpulkan dengan membaca dan membandingkan teks sumber dan teks sasaran secara bersamaan dan dianalisis untuk memastikan memang terjadi kesalahan penerjemahan.data menunjukkan bahwa penyimpangan makna yang paling banyak (64,3%),diikuti oleh perubahan makna (12,8%), penghilangan makna (12,8%),penambahan makna (5,72%)danpembalikan makna (4,3%). Temuan membuat penulis sampai kepada rekomendsi untuk memahai sesuatu dibalk sebuah teks, prraktek metodebelajar analisis kritis yang berkelanjutan dengan menggunakan teks yang beragam supaya kemampuan menerjemah semakin tajam. Kata Kunci: Kesalahan Dalam Penerjemahan, Prosedur Penerjemahan, Bentuk Kesepadanan Dan Analisis Isi.